As implicações do material estruturado NAME nas práticas de alfabetização no ensino inclusivo em Xaxim/SC - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2021)
The research, carried out in 2021, aimed to analyze the implications of the structured material NAME on literacy practices in inclusive education in the city of Xaxim/SC. It was guided by the dialectical method and theorized by the cultural-historical perspective. From this epistemethodological articulation, conversation circles were organized through the didactic way of historical-critical pedagogy. The following procedures were used to carry out the research: a) analysis of a curricular document from the Support Center for Municipalities and States (NAME), used by the municipal education network in Xaxim/SC; b) interview with the secretary of Education of the municipality active in 2005, when the municipality began to adhere to structured materials; c) literature review on literacy and inclusive education; d) ten conversation circles with the city's literacy teachers, lasting 1 hour and 30 minutes each, totaling 15 hours of conversation circles. The results indicate that throughout the history of literacy, inclusive education was not the main scope of debates about teaching reading and writing to students that are the target audience of special education, and that only in 2012, with the institutionalization of the National Pact for Literacy in the Right Age (PNAIC), inclusive education gained ground, even with timid and fragile debates. This meeting between inclusive education and literacy in the PNAIC marked the first moment in which, in Brazil, a public educational policy materialized in a literacy training program, which also has materials that guide teaching practices, opens space for dialogue about school inclusion. In Xaxim/SC, in addition to the PNAIC, the structured materials of NAME guide training and literacy practices, materials that justify the dialogue about inclusive education through illustrations of children with disabilities on the pages of the handouts, but who do not dialogue in their training about this teaching. The data highlight that NAME structured materials incur in the emptying and/or simplification of content, in the precariousness of teaching and continuing education for literacy teachers and in the reinforcement of selective education, one in which some learn and others are only included.
Keywords: Alfabetização no ensino inclusivo; NAME; Materiais e formação de alfabetizadoras; Literacy in inclusive education; NAME; Materials and training for literacy teachers; CNPQ::CIENCIAS HUMANAS::EDUCACAO